Implementation of Medical Record System at UMB Medical Center Bengkulu City - Anugrah Dwi Afriadi; Dandi Sunardi (Jurnal Komputer, Informasi dan Teknologi, 2022)
UMB Media Center (UMC) Bengkulu City is a health company owned by the University of Muhammadiyah Bengkulu. Currently, administrative services provided by UMC Bengkulu City to patients or clients, such as data management and data retrieval related to patients and other medical data, are still carried out manually through recording into administrative notebooks and Microsoft office applications. This has an impact on the orderly and slow management of patient medical record data and the presentation of information. system analysis and design using the Waterfall method which has stages of analysis, design, implementation, testing, deployment, and maintenance so that the UMS medical record application was built with the aim of storing track records of patient health quickly and making it easier to manage patient data..